Evaluation of Treatment Outcomes of HER-2-Positive Breast Cancer Patients from Provincial General Hospital Dr. M. Djamil Padang - Putri, Rizqy Nurfathonah; Harahap, Wirsma Arif; Asri, Aswiyanti (Indonesian Journal of Cancer, 2024)
Background: Human Epidermal Receptor-2 (HER-2) is a member of the human epidermal growth factor receptor family that can be overexpressed or amplified in 15–20% of breast cancer cases. This overexpression or amplification is associated with excessive proliferation and differentiation resulting in more aggression and shortened disease-free survival (DFS) and overall survival (OS). Treatment strategies rely on several factors, including targeting the specific status of biomarkers like HER-2, one example is Trastuzumab. This study aims to evaluate trastuzumab treatment in HER-2 subtype breast cancer patients who received trastuzumab therapy for 6 months compared to patients who did not receive trastuzumab therapy in terms of DSF and OS from 2017 until 2022.Methods: This research employed a retrospective descriptive study using secondary data of 126 patients taken from the medical records of the Provincial General Hospital Dr. M. Djamil Padang and the Cancer Registry of the Indonesian Society of Surgical Oncology, Padang. The inclusion criteria for this study were data on breast cancer patients with HER-2 positive who received trastuzumab therapy for 6 months and patients who did not receive trastuzumab therapy. Patients have complete data including name, gender, age, immunohistochemistry results, and their classification can be determined. This study used univariate analysis and Kaplan-Meier for survival analysis methods.Results: The results of this study showed that the highest age group was over 50 years, the most common histopathological subtype was invasive Carcinoma Mammae of NST (Non-Special Type), and the most frequent TNM stage was Stage II. Patients who received 6 months of trastuzumab therapy had disease-free survival of 46 months (95% CI 39.95–51.15) and an overall survival of 53 months (95% CI 49.19–57.24). In the early stage, the disease-free survival rate was 56 months (95% CI 38.89–56.60), while in a locally advanced stage, the disease-free survival rate was 39 months (95% CI 51.52–61.21).Conclusions: There was a prolongation of disease-free survival and overall survival rates when trastuzumab therapy was given for 6 months. The prognosis of HER-2-positive breast cancer patients in the early stage was better than patients in the locally advanced stage.